Propriedades reológicas e resistência ao cisalhamento de juntas adesivas preparadas com adesivo poliuretano monocomponente para aplicações automotivas - Flores, Camila Campos [UNIFESP] (2015)
In recent years, with increasing competitiveness and quality in the automotive industry, there is an increasing demand for adhesives polyurethane (PU) single component, intended for bonding and grounding glasses (windshields, portholes and other fixed glazing) in body metal and fasteners in general. The use of adhesives for this purpose is mainly related to the reduction of vehicle weight and stimulation of tensioned areas and structural flexibility of vehicles. This study investigated the rheological properties and the shear strength properties of the adhesive joints, composed by different substrates, depending of the relative humidity (RH) and the exposure time. In addition, the chemical-physical tests were done to investigate the curing behavior. The rheological behavior of the adhesive has been studied in order to determine the gel time on nitrogen atmosphere and on ambient atmosphere at (50±5)% RH. Physical-chemical characteristics were measured to investigate the adhesive curing time. In addition to the physical properties that investigate the adhesive curing behavior, the shear strength of the joint was studied by varying the composition of joint as a function of time and RH exposition. The gel time was observed in 6 minutes on ambient atmosphere at (50±5)% and 14 minutes to nitrogen atmosphere . To the shear strength tests was observed that, independent of the joint composition, the average strength, when the joints were exposed at RH (70±5)%, was significantly higher, compared to the strength of the joints exposed at RH (50±5)%.